The temptations of Jesus in early Christianity - Gibson, Jeffrey B. (Sheffield, UK Sheffield Academic, 1995)
Includes bibliographical references and indexes.
Revised version of the author's Oxford DPhil thesis.
Keywords: Jesus Christ -- temptations